Realtà biologica umana - Fagioli, Marcella (Il sogno della farfalla, 2005)
The article proposes some reflection on human biological reality, which differs from that of animals not only because there is a difference in the chromosome pattern but also because thought, understood in its widest sense to also include psychic reality, constitutes a distinct human characteristic. This reflection therefore concentrates on the fact that human reality cannot be understood simply in terms of phycal reality and diversity that exists with other species cannot be explained simply in terms of this physical difference. The conceptualisation and consequent acceptance of the existence of a psychic reality which gives humans their distinct identity, allow us to take on a differente attitude and form a different internal structure than towars a physical handicap. An internal structure which is different and contrasts whith the simple care-giving proposal and the underlying therapeutic nichilism contained in the conviction of an absolute incurability. An inevitable conviction if we choose to define human reality exclusively in terms of physical reality, whereby a physical defect would then imply the loss of human identity and dignity.